2022
DOI: 10.1063/5.0087384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electronic correlation on the high harmonic generation in helium: A time-dependent configuration interaction singles vs time-dependent full configuration interaction study

Abstract: In this paper, we investigate the effects of full electronic correlation on the high harmonic generation in the helium atom subjected to laser pulses of extremely high intensity. To do this, we perform real-time propagations of the helium atom wavefunction using quantum chemistry methods coupled to Gaussian basis sets. The calculations are done within the real-time time-dependent configuration interaction framework, at two levels of theory: time-dependent configuration interation with single excitations (TD-CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…Similarly to our previous works ,,, and to the works of other authors utilizing real-time time-dependent methods to simulate strong-field electron dynamics, ,,,, we employ the heuristic finite lifetime model of Klinkusch et al to compensate for the incompleteness of the atomic orbital basis sets. The electronic energies E k of excited states beyond the ionization threshold are modified by adding imaginary ionization rates E k k = E k i Γ k / 2 goodbreak0em2em⁣ for .25em E k E 0 + I p The finite lifetime model was originally developed for RT-TDCIS and later extended to RT-TDCI with higher excitations. , The ionization rates of CIS states are defined as Γ k = i normalo normalc normalc a normalv normali normalr | X i a k | 2 θ false( ϵ a false) 2 ϵ a / d where θ( x ) is the Heaviside step function and the empirical parameter d represents a maximum distance from the molecule that a (semiclassical) electron can travel before undergoing ionization. Naturally, eq applies to the TDA and INDO/S states as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our previous works ,,, and to the works of other authors utilizing real-time time-dependent methods to simulate strong-field electron dynamics, ,,,, we employ the heuristic finite lifetime model of Klinkusch et al to compensate for the incompleteness of the atomic orbital basis sets. The electronic energies E k of excited states beyond the ionization threshold are modified by adding imaginary ionization rates E k k = E k i Γ k / 2 goodbreak0em2em⁣ for .25em E k E 0 + I p The finite lifetime model was originally developed for RT-TDCIS and later extended to RT-TDCI with higher excitations. , The ionization rates of CIS states are defined as Γ k = i normalo normalc normalc a normalv normali normalr | X i a k | 2 θ false( ϵ a false) 2 ϵ a / d where θ( x ) is the Heaviside step function and the empirical parameter d represents a maximum distance from the molecule that a (semiclassical) electron can travel before undergoing ionization. Naturally, eq applies to the TDA and INDO/S states as well.…”
Section: Methodsmentioning
confidence: 99%
“…RT-TDCIS, being equivalent to the Hartree–Fock (HF) method for excited states, does not account for correlation effects. Although it has been demonstrated that dynamical electron correlation has little effect on the laser-driven dynamics in atoms , and small molecules, ,,,, in the case of C 60 , it is known that the single-determinant restricted HF wave function is not a stable ground state due to global correlations in the π orbital space . Therefore, limiting the calculations solely to RT-TDCIS may not be sufficient to obtain reliable HHG spectra.…”
Section: Introductionmentioning
confidence: 99%
“…HHG is currently exploited for molecular imaging, to discriminate chiral response from enantiomers, to observe changes at the time scale of chemical reactions, and to reveal possible effects due to electron correlation. …”
Section: Introductionmentioning
confidence: 99%
“…Beyond the 3SM, to capture qualitatively and quantitatively fine features of HHG spectra and complexity of the field-induced dynamics requires a first-principle approach. Indeed, real-time time-dependent electronic-structure wavefunction-based methods (RT-TD-WF) have been successfully applied to strong-field electronic dynamics. ,, Time propagation can be carried out in the space of molecular orbitals (MOs) , , or in the space of the field-free eigenstates of the atom or molecule. ,,,, …”
Section: Introductionmentioning
confidence: 99%